2014
DOI: 10.1016/j.drugalcdep.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Left middle frontal gyrus response to inhibitory errors in children prospectively predicts early problem substance use

Abstract: Background A core vulnerability trait for substance use disorder (SUD) is behavioral disinhibition. Error processing is a central aspect of inhibitory control that determines adaptive adjustment of performance; yet it is a largely overlooked aspect of disinhibition as it relates to risk for SUD. We investigated whether differences in brain activation during both successful and failed inhibition predicts early problem substance use. Method Forty-five 9–12 year olds underwent a functional MRI scan during a go/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 46 publications
(72 reference statements)
5
75
0
Order By: Relevance
“…Early maturation of neural features could be considered a vulnerability for youth, increasing the likelihood of engaging in sensation-seeking behaviors at an earlier age. Together, these studies suggest that neurodevelopmentally precocious youth may have a greater tendency to initiate and escalate risk-taking behaviors like substance use relative to peers [33, 7678]. In a separate study, adolescent recent (past 90 day) binge drinkers were found to have reduced posterior cerebellar activity during reward processing above and beyond their baseline substance-naive neural functioning; more drinks per drinking day was related to less cerebellar activation.…”
Section: Neural Features That Follow Adolescent Substance Usementioning
confidence: 95%
See 1 more Smart Citation
“…Early maturation of neural features could be considered a vulnerability for youth, increasing the likelihood of engaging in sensation-seeking behaviors at an earlier age. Together, these studies suggest that neurodevelopmentally precocious youth may have a greater tendency to initiate and escalate risk-taking behaviors like substance use relative to peers [33, 7678]. In a separate study, adolescent recent (past 90 day) binge drinkers were found to have reduced posterior cerebellar activity during reward processing above and beyond their baseline substance-naive neural functioning; more drinks per drinking day was related to less cerebellar activation.…”
Section: Neural Features That Follow Adolescent Substance Usementioning
confidence: 95%
“…fMRI studies on healthy, non-substance using youth have shown that neural circuitry underlying inhibitory control undergoes significant neurodevelopment during adolescence [29, 30]. Longitudinal fMRI studies of youth have shown that even in the presence of comparable performance, abnormal brain activation during inhibition tasks predicts alcohol use by mid-to-late adolescence [3133], future substance use and dependence symptoms [33, 34], and significant alcohol-related consequences like blackouts (i.e., when a person is awake while drunk but does not remember pieces or large sections of time) [35]. Furthermore, less frontal and parietal brain activation on tasks of visual working memory in substance-naive youth have been found to be predictive of greater substance involvement by late adolescence [36].…”
Section: Neural Features That Predate Adolescent Substance Usementioning
confidence: 99%
“…Much of the work using the go/no-go task to investigate familial risk either focuses on successful trials only [19, 22] or does not differentiate between successful and failed no-go trials [18, 23•, 24, 27•]. Recent work by Heitzeg et al [29] extends this literature by differentiating between successful and failed inhibitory (no-go) trials. Participants underwent a baseline scan at age 9–12 years, and those who demonstrated problem substance use by age 13–16 were matched on age, gender, and parental AUD to substance-naive controls.…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…Gender differences were investigated directly in only one study [29], as an exploratory analysis with a small sample of females. No suggestion of a gender difference in the relationship between brain mechanisms involved in inhibitory control and early risk for problem substance use was found in this 9–12-year-old sample; however, evidence in adults indicates that increased thalamic activation during inhibitory errors uniquely marks parental risk in males but not females [36].…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…It is also predictive of later substance use disorders (51). This region is also particularly susceptible to atrophy associated with chronic alcohol use (52).…”
Section: Dorsolateral: Middle Frontal Gyrusmentioning
confidence: 99%